KEEFEKTIFAN PRAUJIAN NASIONAL MATEMATIKA TAHUN AKADEMIK 2004/2005 (Studi Kasus di SMK Negeri dan Swasta di Jakarta Selatan 06) - Hoyyi, Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2009)
National pre-exam is one way of the evaluation to the student’s ability. Through national pre-exam, it would get information how far the student’s preparation to have national exam. National pre-exam is expected to improve student’s score on national exam. In addition, national pre-exam is expected can be used to evaluate student’s preparation and it can predict national examination score. The improving of student’s achievement depends on the way the analysis of change of national examination achievement distribution and description statistics analysis national examination score. The statistics of McNemar’s test is used to know student’s preparation, because the sample is dependent. Correlation and simple linier regression analysis used for analysis prediction. The increase of national examination score not always the effect of pre-national examination. The pre-national examination can’t be used to estimate student’s preparation. The probability student that pass the national exam is higher than pre-national exam. It is caused by pre-national exam is more difficult than national exam through the same passing limit. The score of national exam prediction is obtained confidence limit wide enough. Therefore, the variant national of examination achievements is quite large. Key words: National Pre-exam, National Exam, Description Analysis, McNemar’s Test; Predictionhttp://ejournal.undip.ac.id/index.php/media_statistika/article/view/2481